1997
DOI: 10.2307/3503534
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of the Giant Sand Treader Camel Cricket, Daihinibaenetes giganteus Tinkham (Orthoptera: Rhaphidophoridae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Interestingly, many of the non-singing ensiferans are known to engage in some type of intraspecific communication using substrate-borne vibration, drumming using abdomen or legs, or tremulation (shaking without any substrate) 29 , 49 , 63 , 66 , 67 , and have well-developed chordotonal organs for sensing vibration 7 , 68 . Our analysis also shows that abdomino-femoral stridulation likely evolved at least twice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many of the non-singing ensiferans are known to engage in some type of intraspecific communication using substrate-borne vibration, drumming using abdomen or legs, or tremulation (shaking without any substrate) 29 , 49 , 63 , 66 , 67 , and have well-developed chordotonal organs for sensing vibration 7 , 68 . Our analysis also shows that abdomino-femoral stridulation likely evolved at least twice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(1991); Lawrence et al . (1992); Love & Walker (1979); Marshall & Severin (1906); Maskell (1927); Mason (1961, 1991); Michel (1979, 1980); Morris & Gwynne (1978, 1990); Nesbit (1941); Otte (1992); Qadri (1940); Ragge (1955a,b); Ramme (1931); Rentz (1980, 1993); Rentz & John (1990); Richards (1955, 1961, 1965, 1966, 1973); Saltet (1969); Saussure (1898); Sayce (1898); Schumacher (1978); Schwabe (1906); Sellier (1954); Sinety (1901); Snodgrass (1937); Stål (1876); Strenger (1942); Tindale (1928); Tinkham & Rentz (1969); Uvarov (1966); Wada (1965, 1966); Walker (1962, 1967); Weissmann M. J. (1997); Weissmann D. B.…”
Section: Methodsmentioning
confidence: 99%
“…Jumping spiders are diurnal and active predators of other terrestrial invertebrates (Foelix 1982;Griswold 1987), and they are most commonly found in low vegetation or on sandy substrate near vegetative cover at White Sands. Sand-treader crickets burrow in the daytime and emerge to forage at night (Weissman 1997), and they are commonly found near their burrows at the base of the sand dunes, typically in areas with sparse vegetation cover (E.B.R. and C.E.P., personal observation).…”
Section: Arthropod Phenotypic Convergencementioning
confidence: 99%